Editorial - Bagla, Jasjeet Singh (My University, 2021)
This issue of Resonance celebrates the life and work of Professor Govind Swarup. Govind was one of a kind, in a league of his own, with few people to whom he or his body of work can be compared easily. What made him unique was his ability to see the big picture, as well as, the capability to focus on the subtle aspects of a project. The combination of the ability to dream big, undaunted by the audacious scale of projects, the tenacity to see things to a logical endpoint, and a willingness to work hard through all stages ensured that the projects undertaken by him and his team were successful. He was always willing to collaborate on ventures big and small.
Only IISERM authors are available in the record.
Keywords: Editorial